Asymmetry in the common wall lizard Podarcis muralis under different levels of urbanization: the effect of trait and FA index selection - Mirč, Marko; Tomašević Kolarov, Nataša; Stamenković, Srđan; Vukov, Tanja D. (Archives of Biological Sciences, 2019)
Paper description: Fluctuating asymmetry (FA), as a measure of developmental instability induced by environmental stress, is widely used but with different methodological approaches that result in discordant conclusions. We tested for the first time whether the choice of different fluctuating asymmetry indices and meristic traits affect the assessment of the developmental instability induced by urbanization in the common wall lizard, Podarcis muralis. Different indices and traits can have dissimilar patterns, which can affect conclusions about developmental instability induced by environmental stress. Caution must be practiced when deciding what indices and traits are going to be used for FA analysis. Abstract: The use of fluctuating asymmetry (FA) as a measure of developmental instability and its relationship to stress and fitness is highly controversial. We examined whether the selection of different FA indices and traits influences the results of FA analysis. We chose four meristic traits and three FA indices (two single-trait and two multiple-trait indices) to assess FA levels in the common wall lizard (Podarcis muralis) from three different habitat types (urban, suburban and natural). Urbanization has already been linked to developmental instability in P. muralis. We therefore expected to detect different FA levels among the habitats. However, we also wanted to see whether we obtained the same patterns using different indices and traits. Our results showed that different traits can yield different FA patterns between habitats. The only statistically significant difference between habitats was detected for the FA2 index in femoral pores. The highest level of FA was detected in the urban population, while the lowest level was in the natural population. It is clear that caution must be exerted when deciding on which traits and indices are to be used for FA analysis. https://doi.org/10.2298/ABS190225033M Received: February 25, 2019; Revised: May 22, 2019; Accepted: May 22, 2019; Published online: May 29, 2019 How to cite this article: Mirč M, Tomašević-Kolarov N, Stamenković S, Vukov TD. Asymmetry in the common wall lizard Podarcis muralis under different levels of urbanization: The effect of trait and FA index selection. Arch Biol Sci. 2019;71(3):501-8.